Ratio of maximum hamstring torque to maximum quadriceps torque in professional basketball and soccer players - A. Kukrić; M. Joksimović; B. Petrović; F. Latino; R. Pavlović; R. Kuvalja (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
Purpose: The aim of the study was to determine the differences between football players and basketball players in the mean absolute values ​​of maximum torque flexors and extensors, ratio of maximum hamstring torque to maximum quadriceps torque dominant (DOM) non-dominant (ND) leg and differences in bilateral imbalance of flexor muscles and knee extensors. Material and methods: The research included a sample of 39 professional athletes. The first subsample included 19 professional basketball players while the second subsample included 20 professional soccer players. Results: Based on the results of the torques of the extensors in the knee joint of the DOM and ND legs, it was established that there is no statistically significant difference between basketball players and football players. However, a statistically significant difference was found in the torque flexors of the knee joint DOM (p≤0.01) and ND (p≤0.00) of the leg between basketball players and football players. On the other hand, the results of the research indicate that the difference between basketball players and football players in the ratio of Hamstrings peak torque to Quadriceps peak torque was recorded only in the ND leg (p≤0.02), while the difference in the DOM leg is not statistically significant. The results of our study indicate that basketball players have a higher percentage of imbalances compared to football players, especially in m. hamstrings. Conclusion: This study provides normative data on populations specific to soccer and basketball, but does not provide evidence of the ability of the isokinetic assessment of lower extremity muscle strength to predict injuries to football players and basketball players.